SWOT ANALYSIS OF SMES PRODUCTS PONDOK AL-FATIMAH BOJONEGORO - Bella, Dinda Zalsa; Wulandari, Arumilia; Kurniati, Lestria Ines; Prasetya, Sukma Perdana (International Conference On Social Science Education, 2023)
Al Fatimah Islamic Boarding School Bojonegoro has a business in the form of several SME products engaged in household hygiene products. This is based on the daily activities carried out by residents of Islamic boarding schools. However, in product development, many things could still be improved. This research aims to develop SMEs' Al-Fatimah Islamic boarding school products. This research method uses Qualitative SWOT Analysis. Data sources interviews and direct observation by looking at the strengths, weaknesses, opportunities, and threats of the products produced. This article contains the research results on internal and external factors. Internal results regarding business strengths and weaknesses are obtained, while external results are obtained from business opportunities and threats. In addition, the results of this study also contain a product development strategy for modern Islamic boarding school SMEs Al-Fatimah Bojonegoro in the form of product branding so that the business continues to run.